Updated review of treatment guidelines for schizophrenia in a specialized institute: focus on pharmacological and psychosocial therapies - Revilla-Zúñiga, Joshep (2025)
Schizophrenia is a complex and heterogeneous mental disorder. This article presents an updated review of the main pharmacological and psychosocial recommendations for the management of adult patients withschizophrenia in a level III-2 healthcare facility in Peru. Non-systematic review of the literature recorded on PubMed/MEDLINE, Scopus, EMBASE, Cochrane Library, ScienceDirect, and Google Scholar. The management of schizophrenia in adults requires a pharmacological approach with antipsychotics, which can be administered through oral, rapid-acting or long-acting parenteral routes. Before starting and during the treatment, periodic baseline examinations are recommended. The use of scales also allows the evaluation of antipsychotic response. Regular assessment of adverse/secondary events, such as extrapyramidal symptoms, is recommended. In treatment-resistant schizophrenia, the use of clozapine is recommended. From the psychotherapeutic perspective, individual and group cognitive-behavioural therapy approaches stand out. The clinical management of schizophrenia involves an individualized pharmacological modality, and a non-pharmacological approach that involves both the patient and his/her social context.